The handbook of language variation and change - Chambers, J. K.; Schilling-Estes, Natalie (Wiley-Blackwell, a John Wiley & Sons, Ltd., Publication, 2013)
This handbook, written by a distinguished international roster of contributors, reflects the vitality and growth of the discipline in its multifaceted pursuits. It is a convenient, hand-held repository of the essential knowledge about the study of language variation and change